2000
DOI: 10.4049/jimmunol.165.5.2850
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of DNA Vaccines Determines Their Immunogenicity After Intramuscular Injection in Mice

Abstract: Intramuscular injection of DNA vaccines elicits potent humoral and cellular immune responses in mice. However, DNA vaccines are less efficient in larger animal models and humans. To gain a better understanding of the factors limiting the efficacy of DNA vaccines, we used fluorescence-labeled plasmid DNA in mice to 1) define the macroscopic and microscopic distribution of DNA after injection into the tibialis anterior muscle, 2) characterize cellular uptake and expression of DNA in muscle and draining lymph nod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
191
1
2

Year Published

2000
2000
2013
2013

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 295 publications
(207 citation statements)
references
References 42 publications
13
191
1
2
Order By: Relevance
“…Thus, although ET is known to cause temporary and mild ionic disturbances in muscle, 39 there was no evidence that the ET procedure is able to act as a damageassociated molecular pattern to prime the inflammasome ( Figure 6). The role of the inflammasome in response to ET is an important consideration in DNA vaccine design as ET can enhance DNA vaccine effectivity, 40,41 whereas the action of the important vaccine adjuvant aluminium (alum) is thought to require the inflammasome. 42 For this reason, it will be important to investigate the use of newer ET protocols on the effectivity of vaccine action as it may be possible that, as well as improving plasmid distribution and expression, some damage may be necessary to prime detection of the vaccine plasmid and encoded antigen.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, although ET is known to cause temporary and mild ionic disturbances in muscle, 39 there was no evidence that the ET procedure is able to act as a damageassociated molecular pattern to prime the inflammasome ( Figure 6). The role of the inflammasome in response to ET is an important consideration in DNA vaccine design as ET can enhance DNA vaccine effectivity, 40,41 whereas the action of the important vaccine adjuvant aluminium (alum) is thought to require the inflammasome. 42 For this reason, it will be important to investigate the use of newer ET protocols on the effectivity of vaccine action as it may be possible that, as well as improving plasmid distribution and expression, some damage may be necessary to prime detection of the vaccine plasmid and encoded antigen.…”
Section: Discussionmentioning
confidence: 99%
“…The intracellular distribution of rhodamine signal was primarily localized to endosomal compartments, which is similar to cellular uptake patterns of naked fluorescentlabeled plasmid in vitro, and what has been reported for plasmid taken up by Mac-1 + cells in vivo. 29 The presence of the cationic surfactant on the surface of microparticles may contribute to endosomal disruption and increased cytoplasmic or nuclear localization, although the mechanism of endosomal escape remains unclear. Recently, Newman et al reported cytoplasmic localization of Texas red labeled dextran encapsulated in PLGA microspheres following phagocytosis by mouse peritoneal macrophages.…”
Section: Sf2 Formulated On Plg-ctab Microparticles Following a 24 H mentioning
confidence: 99%
“…A resurgence of interest in spontaneous transgenesis of mammalian cells 18 came with the demonstration that the injection of plasmid DNA intramuscularly or intradermally yields systemic immune responses, 19,20 yet the mechanisms of transgenesis and which cells are susceptible to DNA uptake in vivo remain largely unknown. 21 The present study began with the intention to gain insights into the possible downstream functional effects of spontaneous transgenesis in lymphoid cells. As a model system we used bacterial DNA in the form of a plasmid containing a functional immunoglobulin (Ig) heavy (H) chain gene (the transgene) regulated by a B-cell-specific promoter and human B cells as target.…”
Section: Introductionmentioning
confidence: 99%